REGARDING CATEGORIES OF REFUGEES IN TURKESTAN (LATE 19TH CENTURY, EARLY 20TH CENTURY) - Farrukh SAIDOV (Scholar Express Journal, 2023)
This article analyzes the national-ethnic composition of refugees in Turkestan at the end of the 19th - the beginning of the 20th century and the reasons for the migration through primary sources.
Keywords: Fugitive; fugitives; Turkish; Persian; Armenian